Clinical impact and 'natural' course of uncorrected tricuspid regurgitation after implantation of a left ventricular assist device: an analysis of the European Registry for Patients with Mechanical Circulatory Support (EUROMACS) - Veen, Kevin M; Mokhles, Mostafa M; Soliman, Osama; de By, Theo M M H; Mohacsi, Paul; Schoenrath, Felix; Paluszkiewicz, Lech; Netuka, Ivan; Bogers, Ad J J C; Takkenberg, Johanna J M; Caliskan, Kadir; EUROMACS Investigators (European journal of cardio-thoracic surgery, 2021)
OBJECTIVES: Data on the impact and course of uncorrected tricuspid regurgitation (TR) during left ventricular assist device (LVAD) implantation are scarce and inconsistent. This study explores the clinical impact and natural course of uncorrected TR in patients after LVAD implantation. METHODS: The European Registry for Patients with Mechanical Circulatory Support was used to identify adult patients with LVAD implants without concomitant tricuspid valve surgery. A mediation model was developed to assess the association of TR with 30-day mortality via other risk factors. Generalized mixed models were used to model the course of post-LVAD TR. Joint models were used to perform sensitivity analyses. RESULTS: A total of 2496 procedures were included (median age: 56 years; men: 83%). TR was not directly associated with higher 30-day mortality, but mediation analyses suggested an indirect association via preoperative elevated right atrial pressure and creatinine (P = 0.035) and bilirubin (P = 0.027) levels. Post-LVAD TR was also associated with increased late mortality [hazard ratio 1.16 (1.06-1.3); P = 0.001]. On average, uncorrected TR diminished after LVAD implantation. The probability of having moderate-to-severe TR immediately after an implant in patients with none-to-mild TR pre-LVAD was 10%; in patients with moderate-to-severe TR pre-LVAD, it was 35% and continued to decrease in patients with moderate-to-severe TR pre-LVAD, regardless of pre-LVAD right ventricular failure or pulmonary hypertension. CONCLUSIONS: Uncorrected TR pre-LVAD and post-LVAD is associated with increased early and late mortality. Nevertheless, on average, TR diminishes progressively without intervention after an LVAD implant. Therefore, these data suggest that patient selection for concomitant tricuspid valve surgery should not be based solely on TR grade.
Keywords: dospělí; Mortality; Left ventricular assist device; Adult; výsledek terapie; Heart Failure; Registries; Heart-Assist Devices; Natural course; lidé; srdeční selhání; Treatment Outcome; retrospektivní studie; Male; podpůrné srdeční systémy; Tricuspid Valve Insufficiency; lidé středního věku; registrace; mužské pohlaví; Tricuspid regurgitation; Retrospective Studies; Middle Aged; trikuspidální insuficience; Humans